RESISTANCE TO DIGITAL INNOVATION: A SYSTEMATIC REVIEW IN SCHOOL ENVIRONMENTS - Syah, Maenuddin Bustanil (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
The utilization of digital technology in schools should ideally serve as a major driver for educational transformation. However, resistance to change remains a significant barrier. This study aims to analyze the factors contributing to resistance to the adoption of digital technology in school environments using the Systematic Literature Review (SLR) method. Based on an analysis of 20 publications (5 books and 15 journal articles) selected through specific inclusion-exclusion criteria, this study finds that the main factors of resistance include lack of digital competence, uncertainty about the effectiveness of technology, additional workload, and a conservative organizational culture. These findings indicate the need for more adaptive change strategies based on teacher capacity building and school culture reform. This research provides important contributions to understanding resistance to change and offers practical implications for education managers.